Comparative study of transition metal-doped calcined Malaysian dolomite catalysts for WCO deoxygenation reaction - Hafriz R.S.R.M.; Nor Shafizah I.; Salmiaton A.; Arifin N.A.; Yunus R.; Taufiq Yap Y.H.; Abd Halim S. (Elsevier B.V., 2023)
Calcination; Carbon dioxide; Carboxylation; Gas chromatography; Liquid chromatography; Mass spectrometry; Oils and fats; Physicochemical properties; Temperature programmed desorption; Transition metals; Chemical compositions; Comparative studies; Deoxygenation reactions; Emission microscopy; High selectivity; Mass spectroscopy; Oxygenated compounds; Waste cooking oil; Catalyst selectivity